A Collaborative Approach to Improve Consistent Use of Procalcitonin in Lower Respiratory Tract Infections. Issue 6 (June 2018) - Levine, Alexander R.; Riggott, Robyn; Vulaj, Kristela; Falcetti, Tera R.; Ali, Syed; Singh, Gagandeep
Background: Procalcitonin (PCT) is a biomarker that can help differentiate bacterial from viral infections and has been extensively studied in patients with sepsis and pneumonia to guide antibiotic therapy. However, there is poor adherence to prescribed algorithms when used to discontinue antibiotics in the real world. A quality improvement project was implemented to increase consistent use of PCT.Objective: To evaluate use of PCT and impact on antibiotic length of therapy (LOT) preimplementation and postimplementation of a quality improvement initiative.Methods: This was a single-center retrospective cohort study in patients with lower respiratory tract infections (LRTIs).Results: In all, 330 patients were included in this study. Following implementation of the quality improvement initiative, ordering PCT in the first 24 hours increased from 59.6% to 75.5% ( P = 0.011). Documentation to discontinue antibiotics in patients with low initial PCT values increased from 13.2% to 28.6% ( P = 0.100). Increased PCT use correlated with an overall mean reduction of 1.05 antibiotic days between cohorts (6.82 ± 3.88 vs 5.77 ± 3.43, P = 0.028). There was no difference in incidence of antibiotic-associated adverse effects or 30-day hospital readmission rates attributed to pneumonia.Conclusions: Consistent use of PCT was achieved through a collaborative effort with the clinical pharmacy and hospitalist staff. Increased use of PCT was associated with a significant reduction in antibiotic LOT among patients with LRTIs. When controlling for other factors, low initial PCT values had the strongest influence on discontinuing antibiotics within 72 hours in the intervention group.